Dexamethasone Sensitizes Acute Monocytic Leukemia Cells to Ara-C by Upregulating FKBP51 - Sun, Huanxin; Liu, Xiaowen; Wang, Laicheng; Cui, Bin; Mu, Wenli; Xia, Yu; Liu, Shuang; Liu, Xin; Jiao, Yulian; Zhao, Yueran (Frontiers in Oncology, 2022)
In this study, we demonstrated that the expression of FK506 binding protein 51 (FKBP51) is upregulated in acute monocytic leukaemia (AML-M5) cells by dexamethasone and aimed to investigate the possible effects of FKBP51 on the growth and cytarabine sensitivity of AML-M5 cells. THP-1 and U937cells were used to establish AML-M5 cell models with FKBP51 overexpression and knockdown, respectively. Cell proliferation, apoptosis and response to cytarabine were investigated by cell cycle, CCK-8 and Flow cytometry analyses. The mice experiment was conducted to detect the role of FKBP51 on AML-M5 cells proliferation and antileukemia effect of Ara-C/ Dexamethasone co-therapy in vivo. Western blots were employed to determine protein expression levels. FKBP51 upregulation significantly attenuated THP-1 cell proliferation and sensitized the cells to cytarabine treatment which was further enhanced by dexamethasone. These effects were indicated by decreases in cell viability, S-G2/M phase cell cycle distribution, cytarabine 50% inhibitory concentration (IC50) values and increases in apoptosis were supported by decreased phosphorylation levels of AKT, GSK3β and FOXO1A and decreased levels of BCL-2 and increased levels of P21 and P27. In contrast, FKBP51 knockdown led to excessive U937 cell proliferation and cytarabine resistance, as indicated by increased cell viability and S-G2/M phase cell cycle distribution, decreased apoptosis, increased phosphorylation levels of AKT, GSK3β and FOXO1A, and increased BCL-2 and decreased P21 and P27 expression. In addition, an AKT inhibitor blocked cell cycle progression and reduced cell viability in all groups of cells. Furthermore, SAFit2, a specific FKBP51 inhibitor, increased U937 cell viability and cytarabine resistance as well as AKT phosphorylation. In conclusion, FKBP51 decelerates proliferation and improves the cytarabine sensitivity of AML-M5 cells by inhibiting AKT pathways, and dexamethasone in combination with Ara-C improves the chemosensitivity of AML-M5.